Productivity of Mountain Reedbugk Redunca Fulvorufula (Afzelius, 1815) at the Mountain Zebra National Park - J. D Skinner (Koedoe: African Protected Area Conservation and Science, 1980)
Eighty two adult mountain reedbuck Redunca fulvoru- fula were collected during four seasons, autumn, winter, spring and summer at the Mountain Zebra National Park mainly during 1975 and 1976. Body mass and carcass characteristics varied little with season, body mass varying from 24,0-35,5 kg for all buck shot and dressing percentage always exeeded 50. According to KFI animals were all in fair to good condition. Sixty four percent of all ewes were pregnant and 38,5 lactating. Females and males bred throughout the year but there was a peak in births during mid-summer. The species is highly productive, well adapted to the niche it occupies and lends itself to exploitation for meat production.